Some aspects of carbide precipitation and phosphorus grain boundary segregation in Cr-V low alloy steels - Výrostková, Anna (Kovine zlitine tehnologije, 1999)
Phosphorus grain boundary segregation was investigated at 773 and 853 K for three Cr-V low alloy steels with different vanadium contents. AES and TEM methods were used for determination of the segregating elements enrichment on grain boundaries and phase identification, respectively. Phosphorus segregation enthalpy and entropy, as well as the phase equilibria for both temperatures, were determined by means of thermodynamic calculations. Aging upto 1000 hours was sufficient to achieve the equilibrium state of phosphorus segregation at the ageing temperatures. In agreement with Langmouir-McLean theory, the phosphorus grain boundary equilibrium concentration decreases with the temperature. The ageing conditions, however, were not sufficient to achieve the phase equilibrium. According to thermodynamic calculations, the steels should consist of ferrite, ?M_7C_3$? and MC (?$M_7C_3$? only in one state at higher ageing temperature) were found experimentally. Chemical composition changes of analysed carbides also confirmed the non-equilibrium state of precipitation. The changes accompanying the non-equilibrium development of phases show a direct influence on phosphorus segregation, specially at 773 K. As a consequence, the supporting effect of vanadium on phosphorus segregation, observed at 853 K is not clear at this low temperature.
Keywords: legirano jeklo; karbidi; kristalizacija; precipitacija; segregacija; fosfor